Risk and survival of patients with medullary thyroid cancer: National perspective. (August 2018) - Al-Qurayshi, Zaid; Khadra, Helmi; Chang, Kristi; Pagedar, Nitin; Randolph, Gregory W.; Kandil, Emad
Highlights: Older age, male, and Black racial background are associated with a higher risk of medullar thyroid carcinoma (MTC). Neck dissection has a crucial role as a staging and therapeutic procedure. Thyroidectomy has more than palliative role in late stage MTC. Radiotherapy was not associated with improved survival in stage IV MTC. Abstract: Background: Medullary thyroid carcinoma (MTC) is a neuroendocrine tumor account for 1–2% of thyroid cancer. In this study, we aim to examine the characteristics and survival of patients with MTC. Methods: A retrospective cohort study utilizing the National Cancer Data Base, 2004–2014. The study population included adults with either MTC (cases) or with differentiated thyroid cancer (DTC) (controls). Results: A total of 2, 776 MTC and 171, 631 DTC patients were included. The median follow-up time for MTC was 55.5 months (interquartile range: 31.2–84.6 months). As compared to DTC, patients with MTC were more likely to be ≥ 45-year old, male, and Black ( p < 0.001). Neck dissection improved survival in patients with stage III [HR: 0.26, 95%CI: (0.10, 0.64), p = 0.004]. In patients with stages I and II, neck dissections did not add significant survival benefit to thyroidectomy [stage I, HR: 1.00, 95%CI: (0.54, 1.86), p = 0.99], [stage 2, HR: 0.72, 95%CI: (0.40, 1.29), p = 0.27]. However, neck dissections upgraded staging to N1A and N1B in 17.7% and 14.3% of patients with clinically N0 neck, respectively. In stage IV, thyroidectomy with neck dissection had the highest 5-year survival (84.9%), but this was not significantly different from thyroidectomy alone (84.1%); Patients who had thyroidectomy and EBRT with or without neck dissection had a lower survival than thyroidectomy alone ( p < 0.01). Conclusions: Neck dissection performed on patients with clinically N0 neck, is important for accurate staging and associate with improved survival in advanced stages. Thyroidectomy and neck dissection in stage IV not only have palliative role but also add survival advantage.